Cultura Visual, hibridismo e a passividade da visão em tempos tecnológicos (Revista Apotheke, 2018)
In this article I intend to reflect on the hybridisms present in the field of Visual Culture, both in its transdisciplinary relations and in the contact with technology for the placement and creation of images. The passivity of the vision is posed as a provocation to think about the relation between the images that we see and our subjectivity, aiming to understand these relations not only through a cultural and social bias, but considering that there are inherent functions of the human brain that participate in this network of meanings. The article points out the teaching of the Visual Arts and Visual Culture as an important tool for the reflection about the images and the social behavior itself in the contemporaneity.
Keywords: visual culture; hybridism; technology; visuality; visual art teaching